(untitled) (Research, Society and Development, 2021)
Objectives: To characterize the epidemiological profile of the population diagnosed with meningitis in the 7th Regional Health Department in the State of Paraná between 2010 and 2019. Materials and Methods: Descriptive-retrospective study based on data available in the Notifiable Diseases Information System (SINAN) between 2010 and 2019, considering the variables: general detection, gender, race, age, diagnostic criteria, etiology and outcome. Data were tabulated in Microsoft Excel and Microsoft Word software. Results: 252 new cases of meningitis were reported at the 7th Regional Health Department of the State of Paraná during the study period, with 63.1% being male and 83.7% declared white. Regarding the age group, 25.1% of the notifications occurred in children under 01 years of age. Of the 252 cases, 36.1% were due to viral agents and 146 were confirmed through CSF chemocytology. Most patients progressed to hospital discharge and 13 cases progressed to death, all of them presenting a bacterial etiology. Discussion and conclusion of the study: Serious and temporally unlimited disease, meningitis is a public health problem, and knowing those most affected by it is essential to guide health services in the development of prevention measures and health education.